EXPRESSION OF CALCITONIN GENE RELATED PEPTIDE (CGRP) IN SMALL NEURONS OF TRIGEMINAL GANGLION AND ITS IMPLICATIONS IN MIGRAINE - SANKARAN PK; JEEVAPRIYA. T; VINAY JADHAV (International Journal of Pharma and Bio Sciences, 2016)
CGRP is a neuropeptide present in the central and peripheral nervous system that has diverse functions as primary afferent neurotransmitter which is important in nociception. Migraine is a neurovascular disorder involving trigeminal ganglion characterized by recurrent episodic headache and a rise in levels of CGRP in plasma. In this study expression of CGRP was studied in neurons of trigeminal ganglion in male wistar albino rats. CGRP is expressed in cytoplasm of neurons mainly in the small sized neurons indicating that small sized neurons are involved in nociception.